(untitled) (European Journal of Economics, Finance and Business Development, 2025)
In the context of increasing digital transformation in the banking sector, the stability of bank deposits has become a key indicator of financial resilience and customer confidence. This article explores the role of digital technologies in enhancing the stability and sustainability of deposit operations in commercial banks. The study emphasizes the integration of artificial intelligence, big data analytics, and digital ecosystems in optimizing deposit portfolio management, predicting customer behavior and reducing liquidity risks. By employing a comparative analysis of international and national banking practices, the research identifies how digital tools such as mobile banking platforms, personalized deposit products and automated risk assessment systems contribute to deposit growth and retention. Moreover, the paper presents a conceptual model that links digital innovation with deposit stability through improved operational efficiency, transparency and trust in digital financial services. The findings suggest that the adoption of advanced digital solutions not only strengthens deposit base stability but also supports the competitiveness and long-term sustainability of commercial banks in a rapidly evolving financial environment.